Drug Protection Automation and Intelligence - Pawar, Kiran A. (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 3 No 1 (2019): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
The Adverse Drug Reaction(ADR) form is the basis text for the Pharmaco vigilance Program of India (PvPI), which imprisonments info first hand from the patient. The raw data afterward entry into Vigiflow makes an Individual Case Safety Reports (ICSR). Henceforth, to enterprise and instrument information extraction about opposing drug effect from ICSR reports is very required to support Pharmacovigilance program. The chief aim of our suggest system is to focus on machine learning based info extraction. This project works professionally on different inputs like Portable Document Format (PDF), text and word document. Output of the system is removed in the form of excel sheet. The system makes use of different algorithms such as Natural Language Processing(NLP)for Extraction, Machine- Learning for Classification, Artificial Intelligence(AI) for learning and accuracy. It too usages ADR dictionary such as Medical Regulatory Happenings (MedRA) to achieve execution of the application. How to cite this article: Pawar KA, Pawar PR, Bhumre VD et al. Drug Protection Automation and Intelligence. J Adv Res Appl Arti Intel Neural Netw 2019; 3(1): 30-33